Some remarks on the monotonicity of primary matrix functions on the set of symmetric matrices


This note contains some observations on primary matrix functions and different notions of monotonicity with relevance toward constitutive relations in nonlinear elasticity. Focusing on primary matrix functions on the set of symmetric matrices, we discuss and compare different criteria for monotonicity. The demonstrated results are particularly applicable to computations involving the true-stress–true-strain monotonicity condition, a constitutive inequality recently introduced in an Arch. Appl. Mech. article by C.S. Jog and K.D. Patil. We also clarify a statement by Jog and Patil from the same article which could be misinterpreted.

This is a preview of subscription content, access via your institution.


  1. 1.

    Here and throughout the article, we identify the Fréchet derivative \(DW[X]\) of a function \(W:{{\mathrm{Sym}}}(n)\rightarrow \mathbb {R}\) at \(X\in {{\mathrm{Sym}}}(n)\) with the uniquely determined \(S\in {{\mathrm{Sym}}}(n)\) such that \(DW[X].H=\left\langle S,H \right\rangle \) for all \(H\in {{\mathrm{Sym}}}(n)\).

  2. 2.

    For a more general definition of primary matrix functions for non-symmetric arguments, we refer to [11], Ch. 6.2].

  3. 3.

    Note that \(S_\mathbb {R}={{\mathrm{Sym}}}(n)\) and \(S_{\mathbb {R}^+}={{\mathrm{PSym}}}(n)\).

  4. 4.

    The Valanis-Landel hypothesis was introduced by K.C. Valanis and R.F. Landel in 1967 as an assumption on the elastic energy potential of incompressible materials [31]. Their hypothesis was later found to be in good agreement with the elastic behavior of vulcanized rubber [30]; D.F. Jones and L.R.G. Treloar concluded that “the hypothesis is valid over the range covered” in their experiments, “namely \(\lambda =0.189-2.62_5\)” [13].

  5. 5.

    A formula for the derivative \(D\log [A]\). \(H\) in a direction \(H\) for commuting \(A\) and \(H\) as well as some properties of derivatives of primary matrix functions in arbitrary directions can be found in much earlier works by Richter [28, 29]; however, Richter did not give the more general formula used here.


  1. 1.

    Anand, L.: On H. Hencky’s approximate strain energy function for moderate deformations. J. Appl. Mech. 46, 78–82 (1979)

    Article  MATH  Google Scholar 

  2. 2.

    Anand, L.: Moderate deformations in extension-torsion of incompressible isotropic elastic materials. J. Mech. Phys. Solids 34, 293–304 (1986)

    Article  Google Scholar 

  3. 3.

    Bhatia, R.: Matrix Analysis. Graduate Texts in Mathematics. Springer, New York (1997)

    Google Scholar 

  4. 4.

    Brown, A.L., Vasudeva, H.L.: The calculus of operator functions and operator convexity. Dissertationes Mathematicae. Instytyt Matematyczny PAN (2000)

  5. 5.

    Davis, C.: All convex invariant functions of hermitian matrices. Archiv der Mathematik 8(4), 276–278 (1957)

    Article  MATH  Google Scholar 

  6. 6.

    Ghiba, I.D., Neff, P., Šilhavý, M.: The exponentiated Hencky-logarithmic strain energy. Improvement of planar polyconvexity. Int. J. Non-Linear Mech. 71, 48–51 (2015)

    Article  Google Scholar 

  7. 7.

    Hencky, H.: Welche Umstände bedingen die Verfestigung bei der bildsamen Verformung von festen isotropen Körpern? Zeitschrift für Physik 55, 145–155 (1929).

  8. 8.

    Higham, N.J.: Functions of Matrices: Theory and Computation. Society for Industrial and Applied Mathematics, Philadelphia (2008)

    Google Scholar 

  9. 9.

    Hill, R.: Constitutive inequalities for isotropic elastic solids under finite strain. Proc. R. Soc. Lond. 314, 457–472 (1970)

    Article  MATH  Google Scholar 

  10. 10.

    Hill, R.: Aspects of invariance in solid mechanics. Adv. Appl. Mech. 18, 1–75 (1978)

    Article  MATH  Google Scholar 

  11. 11.

    Horn, R.A., Johnson, C.R.: Topics in Matrix Analysis. Cambridge University Press, Cambridge (1994)

    Google Scholar 

  12. 12.

    Jog, C.S., Patil, K.D.: Conditions for the onset of elastic and material instabilities in hyperelastic materials. Arch. Appl. Mech. 83(5), 661–684 (2013)

    Article  MATH  Google Scholar 

  13. 13.

    Jones, D.F., Treloar, L.R.G.: The properties of rubber in pure homogeneous strain. J. Phys. D Appl. Phys. 8(11), 1285 (1975)

    Article  Google Scholar 

  14. 14.

    Lewis, A.S.: Derivatives of spectral functions. Math. Oper. Res. 21(3), 576–588 (1996)

    MathSciNet  Article  MATH  Google Scholar 

  15. 15.

    Lurie, A.I.: Nonlinear Theory of Elasticity. Elsevier, Amsterdam (2012)

    Google Scholar 

  16. 16.

    Magnus, J.R.: On differentiating eigenvalues and eigenvectors. Econom. Theory 1, 179–191, 8 (1985)

  17. 17.

    Mathias, R.: A symmetry property of the Frechét derivative. Proc. Am. Math. Soc. 120, 1067–1070 (1994)

    MathSciNet  MATH  Google Scholar 

  18. 18.

    Neff, P.: Mathematische Analyse multiplikativer Viskoplastizität. Ph.D. Thesis, Technische Universität Darmstadt. Shaker Verlag, Aachen (2000).

  19. 19.

    Neff, P.: Convexity and coercivity in nonlinear, anisotropic elasticity and some useful relations. Technical report, Technische Universität Darmstadt (2008).

  20. 20.

    Neff, P., Eidel, B., Martin, R.: The axiomatic deduction of the quadratic Hencky strain energy by Heinrich Hencky (a new translation of Hencky’s original German articles) (2014). arXiv:1402.4027

  21. 21.

    Neff, P., Eidel, B., Martin, R.J.: Geometry of logarithmic strain measures in solid mechanics (2015). arXiv:1505.02203

  22. 22.

    Neff, P., Eidel, B., Osterbrink, F., Martin, R.: A Riemannian approach to strain measures in nonlinear elasticity. Comptes Rendus Mécanique 342(4), 254–257 (2014)

    Article  Google Scholar 

  23. 23.

    Neff, P., Ghiba, I.D.: The exponentiated Hencky-logarithmic strain energy. Part III: coupling with idealized isotropic finite strain plasticity. To appear in Continuum Mechanics and Thermodynamics (2015). arXiv:1409.7555

  24. 24.

    Neff, P., Ghiba, I.D., Lankeit, J.: The exponentiated Hencky-logarithmic strain energy. Part I: constitutive issues and rank-one convexity. To appear in J. Elast. (2015). doi:10.1007/s10659-015-9524-7. arXiv:1403.3843

  25. 25.

    Neff, P., Ghiba, I.D., Lankeit, J., Martin, R.J., Steigmann, D.J.: The exponentiated Hencky-logarithmic strain energy. Part II: coercivity, planar polyconvexity and existence of minimizers. To appear in Zeitschrift für angewandte Mathematik und Physik (2015). arXiv:1408.4430

  26. 26.

    Norris, A.N.: Eulerian conjugate stress and strain. J. Mech. Mater. Struct. 3(2), 243–260 (2008)

    MathSciNet  Article  Google Scholar 

  27. 27.

    Norris, A.N.: Higher derivatives and the inverse derivative of a tensor-valued function of a tensor. Q. Appl. Math. 66, 725–741 (2008)

    MathSciNet  Article  MATH  Google Scholar 

  28. 28.

    Richter, H.: Zum Logarithmus einer Matrix. Archiv der Mathematik 2(5), 360–363 (1949).

  29. 29.

    Richter, H.: Über Matrixfunktionen. Math. Ann. 122(1), 16–34 (1950)

    MathSciNet  Article  MATH  Google Scholar 

  30. 30.

    Treloar, L.R.G.: The elasticity and related properties of rubbers. Rep. Prog. Phys. 36(7), 755 (1973)

    Article  Google Scholar 

  31. 31.

    Valanis, K.C., Landel, R.F.: The strain-energy function of a hyperelastic material in terms of the extension ratios. J. Appl. Phys. 38(7), 2997–3002 (1967)

    Article  Google Scholar 

Download references


We thank Prof. Chandrashekhar S. Jog (Indian Institute of Science) for interesting discussions on the topic of constitutive inequalities as well as Prof. Karl-Hermann Neeb (University of Erlangen) and Prof. Nicholas Higham (University of Manchester) for their helpful remarks.

Author information



Corresponding author

Correspondence to Robert J. Martin.



On the derivative of the determinant function

Consider the first-order approximation

$$\begin{aligned} \det (A+H) = \det A + D\det [A].H + \underbrace{\cdots }_{{\begin{array}{c} \text {higher order}\\ \text {terms} \end{array}}} \end{aligned}$$

of the determinant function at a diagonal matrix \(A={{\mathrm{diag}}}(a_1,\ldots ,a_n)\). First we assume that \(H\in {{\mathrm{Sym}}}(n)\) is an off-diagonal matrix of the form

$$\begin{aligned} H = H^{\mathrm {off}} = \left( {\begin{matrix} 0&{}&{}h\\ {} &{}\ddots &{}\\ h&{}&{}0 \end{matrix}}\right) \end{aligned}$$

with \(h\in \mathbb {R}\). We compute

$$\begin{aligned}&\det \begin{pmatrix} \vec {a}_1 + \left( {\begin{matrix} 0\\ \vdots \\ h \end{matrix}}\right) , \, \vec {a}_2\,\,,\,\, \cdots \,\,, \,\, \vec {a}_n + \left( {\begin{matrix} h\\ \vdots \\ 0 \end{matrix}}\right) \end{pmatrix} \nonumber \\&\quad = \det \left( \vec {a}_1, \, \vec {a}_2, \, \cdots , \, \vec {a}_n + \left( {\begin{matrix} h\\ \vdots \\ 0 \end{matrix}}\right) \right) \,+\, \det \left( \left( {\begin{matrix} 0\\ \vdots \\ h \end{matrix}}\right) , \, \vec {a}_2, \, \cdots , \, \vec {a}_n + \left( {\begin{matrix} h\\ \vdots \\ 0 \end{matrix}}\right) \right) \nonumber \\&\quad = \det \left( \vec {a}_1, \, \vec {a}_2, \, \cdots , \, \vec {a}_n \right) \,+\, \det \left( \vec {a}_1, \, \vec {a}_2, \, \cdots , \, \vec {a}_n + \left( {\begin{matrix} h\\ \vdots \\ 0 \end{matrix}}\right) \right) \nonumber \\&\quad \;\;+\, \det \left( \left( {\begin{matrix} 0\\ \vdots \\ h \end{matrix}}\right) , \, \vec {a}_2, \, \cdots , \, \vec {a}_n \right) \,+\, \det \left( \left( {\begin{matrix} 0\\ \vdots \\ h \end{matrix}}\right) , \, \vec {a}_2, \, \cdots , \, \left( {\begin{matrix} h\\ \vdots \\ 0 \end{matrix}}\right) \right) . \end{aligned}$$

Since \(A\) is diagonal by assumption, the column vector \(\vec {a}_1\) has the form \(\vec {a}_1 = \begin{pmatrix} a_{1}&\cdots&0 \end{pmatrix}^T\) and \(\vec {a}_n\) has the form \(\vec {a}_n = \begin{pmatrix} 0&\cdots&a_{n} \end{pmatrix}^T\). Therefore the vectors \(\vec {a}_1\) and \(\begin{pmatrix} h&\cdots&0 \end{pmatrix}^T\) as well as \(\vec {a}_n\) and \(\begin{pmatrix} 0&\cdots&h \end{pmatrix}^T\) are linearly dependent. Thus (18) reduces to

$$\begin{aligned} \det \left( \vec {a}_1, \, \vec {a}_2, \, \cdots , \, \vec {a}_n\right) \,+\, \det \left( \left( {\begin{matrix} 0\\ \vdots \\ h \end{matrix}}\right) , \, \vec {a}_2, \, \cdots , \, \left( {\begin{matrix} h\\ \vdots \\ 0 \end{matrix}}\right) \right) \,=\, \det A \,+\, \underbrace{\det \left( \left( {\begin{matrix} 0\\ \vdots \\ h \end{matrix}}\right) , \, \vec {a}_2, \, \cdots , \, \left( {\begin{matrix} h\\ \vdots \\ 0 \end{matrix}}\right) \right) }_{=:R(h)}. \end{aligned}$$

The term \(R(h)\) is quadratic in \(h\), thus the linear approximation is simply

$$\begin{aligned} D\det [A].H = 0 \end{aligned}$$

for a matrix \(H\in {{\mathrm{Sym}}}(n)\) of the form (17). Through similar computations, it is easy to show that \(D\det [A].H = 0\) for any off-diagonal \(H\in {{\mathrm{Sym}}}(n)\).

To find the derivative \(D\det [A].1\!\!1\) we compute

$$\begin{aligned} \det (A+h1\!\!1)&= \det \left( {\begin{matrix} a_1+h &{} &{}0\\ {} &{}\ddots &{}\\ 0&{}&{}a_n+h \end{matrix}}\right) = \prod _{i=1}^n (a_i+h) = \prod _{i=1}^n a_i + \left( \sum _{i=1}^n\prod _{\begin{array}{c} j=1\\ j\ne i \end{array}}^n a_j\right) \cdot h + h^2\cdot [\dots ], \end{aligned}$$


$$\begin{aligned} D\det [A].1\!\!1 = \frac{\mathrm {d}}{\mathrm {dh}}\det (A+h1\!\!1) = \sum _{i=1}^n \prod _{\begin{array}{c} j=1\\ j\ne i \end{array}}^n a_j. \end{aligned}$$

For \(n=3\) we obtain

$$\begin{aligned} D\det [A].1\!\!1 = a_1 a_2 + a_2 a_3 + a_1 a_3. \end{aligned}$$

Furthermore, if we assume that 0 is a simple eigenvalue of \(A\) [which is the case for matrices of the form \(D-\lambda _i(D) 1\!\!1\) where \(D\) is a diagonal matrix with simple eigenvalues; such matrices appear in Eq. (22)], then (19) can be written as

$$\begin{aligned} D\det [A].1\!\!1 = \prod _{\begin{array}{c} j=1\\ j\ne k \end{array}}^n a_j \ne 0, \end{aligned}$$

where 0 is the \(k\)th eigenvalue of \(A\).

On the derivative of isotropic functions

Lemma 7.1

Let \(W:{{\mathrm{Sym}}}(n)\rightarrow \mathbb {R}\) be an isotropic real valued function, i.e.


$$\begin{aligned} DW[Q^TXQ] = Q^TDW[X]Q. \end{aligned}$$


We directly compute:

$$\begin{aligned}&W(Q^T(X+H)Q) = W(X+H)\\&\quad \Rightarrow W(Q^TXQ + Q^THQ) = W(X) + \left\langle DW[X],\,H \right\rangle + \cdots \\&\quad \Rightarrow \mathop {\overbrace{W(Q^TXQ)}}\limits ^{{=W(X)}} + \left\langle DW[Q^TXQ],\,Q^THQ \right\rangle + \cdots = W(X) + \left\langle DW[X],\,H \right\rangle + \cdots \\&\quad \Rightarrow \left\langle DW[Q^TXQ],\,Q^THQ \right\rangle = \left\langle DW[X],\,H \right\rangle \\&\quad \Rightarrow \left\langle QDW[Q^TXQ]Q^T,\,H \right\rangle = \left\langle DW[X],\,H \right\rangle . \end{aligned}$$

Since this holds for all \(H\in {{\mathrm{Sym}}}(n)\), we obtain

$$\begin{aligned} QDW[Q^TXQ]Q^T = DW[X] \end{aligned}$$

and thus

$$\begin{aligned} DW[Q^TXQ] = Q^TDW[X]Q. \end{aligned}$$

\(\square \)

The eigenvalue function

We could also try to prove Proposition 2.5 for the more general case of non-analytic functions by directly computing the derivative of the function

$$\begin{aligned} W: {{\mathrm{Sym}}}(n)\rightarrow \mathbb {R},\quad W(A) = \sum _{i=1}^n F(\lambda _i(A)). \end{aligned}$$

Unfortunately, while the derivative of \(W\) at a point \(A\in {{\mathrm{Sym}}}(n)\) in directions \(H\) can be explicitly computed if \(A\) and \(H\) commute, it is difficult to do so for arbitrary choices of \(H\in {{\mathrm{Sym}}}(n)\).

One possible approach is to assume that the function \(\lambda : {{\mathrm{Sym}}}(n)\rightarrow \mathbb {R}^n\) mapping a matrix \(M\in {{\mathrm{Sym}}}(n)\) to its (ordered) eigenvalues \(\lambda (M)\) is differentiable in a neighborhood of \(A\in {{\mathrm{Sym}}}(n)\). For example, this is the case if all eigenvalues of \(A\) are simple [16]. The basic idea is to write \(W(A) = \Psi (\lambda (A))\) with \(\Psi (\lambda _1,\ldots ,\lambda _n)=\sum _{i=1}^n F(\lambda _i)\). Then

$$\begin{aligned} DW[A] = D\Psi [\lambda (A)] \cdot D\lambda [A]. \end{aligned}$$

It is therefore useful to compute the derivative \(D\lambda [A]\) of the eigenvalue function. Since Lemma 7.1 implies

$$\begin{aligned} \lambda (Q^TAQ) = \lambda (A) \,\Longrightarrow \, D\lambda [Q^TAQ] = Q^T\,D\lambda [A]\,Q, \end{aligned}$$

the derivative of \(\lambda \) at \(A\) is determined by the derivative at the diagonal matrix corresponding to \(A\). We will therefore assume w.l.o.g. that \(A\) is already a diagonal matrix.

The eigenvalues \(\lambda _i\) of \(A\) are characterized by

$$\begin{aligned} \det (A-\lambda _i 1\!\!1)=0. \end{aligned}$$

Let \(H\in {{\mathrm{Sym}}}(n)\). We compute the first-order approximation of (21):

$$\begin{aligned}&\det (A+H - \lambda _i(A+H)\cdot 1\!\!1) = 0 \nonumber \\&\quad \Rightarrow \, \det (A+H-[\lambda _i(A)1\!\!1 + [D\lambda _i(A).H]\cdot 1\!\!1 + \cdots ]) = 0 \nonumber \\&\quad \Rightarrow \, \det ([A-\lambda _i(A)1\!\!1]+H-[D\lambda _i(A).H]\cdot 1\!\!1 + \cdots ) = 0 \nonumber \\&\quad \Rightarrow \, \underbrace{\det [A-\lambda _i(A)1\!\!1]}_{=0} + \left\langle {{\mathrm{Cof}}}[A-\lambda _i(A)1\!\!1],\, H-[D\lambda _i(A).H]\cdot 1\!\!1 + \cdots \right\rangle + \cdots = 0. \end{aligned}$$

By ignoring higher-order terms we obtain

$$\begin{aligned} \left\langle {{\mathrm{Cof}}}[A-\lambda _i(A)1\!\!1],\, H-[D\lambda _i(A).H]\cdot 1\!\!1 \right\rangle = 0 \end{aligned}$$

Recall that \(A\) is diagonal by assumption. Since \(A\) commutes with diagonal matrices \(H\) (and thus the derivative \(DW[A].H\) could be computed by more direct means), we are only interested in cases where the symmetric matrix \(H\) is off-diagonal, i.e. \(H_{i,i}=0\) for \(i=1,\ldots ,n\). But then

$$\begin{aligned} \langle {\,\underbrace{{{\mathrm{Cof}}}[A-\lambda _i(A)1\!\!1]}_{\text {diagonal}},\, \underbrace{H}_{{\text {off-diagonal}}}}\rangle = 0, \end{aligned}$$

thus (23) reduces to

$$\begin{aligned} \left\langle {{\mathrm{Cof}}}[A-\lambda _i(A)1\!\!1],\, [D\lambda _i(A).H]\cdot 1\!\!1 \right\rangle = 0, \end{aligned}$$

which we can also write as

$$\begin{aligned} (D\lambda _i(A).H)\cdot {{\mathrm{tr}}}\left( {{\mathrm{Cof}}}[A-\lambda _i(A)1\!\!1]\right) = 0. \end{aligned}$$

To conclude that \(D\lambda _i(A).H=0\) it remains to show that \({{\mathrm{tr}}}\left( {{\mathrm{Cof}}}[A-\lambda _i(A)1\!\!1]\right) \ne 0\). Assuming that the diagonal entries of \(A\) are ordered we write \(A={{\mathrm{diag}}}(\lambda _1, \ldots , \lambda _n)\) and find

$$\begin{aligned} A - \lambda _i(A)1\!\!1 = \begin{pmatrix} \lambda _1-\lambda _i &{} &{} 0\\ &{} \ddots &{} \\ 0 &{} &{} \lambda _n-\lambda _i \end{pmatrix} \end{aligned}$$

and thus

$$\begin{aligned} {{\mathrm{Cof}}}[A - \lambda _i(A)1\!\!1] = \begin{pmatrix} \prod \limits _{k\ne 1}(\lambda _k-\lambda _i) &{} &{} 0\\ &{} \ddots &{} \\ 0 &{} &{} \prod \limits _{k\ne n}(\lambda _k-\lambda _i) \end{pmatrix}. \end{aligned}$$

We compute the trace:

$$\begin{aligned} {{\mathrm{tr}}}\left( {{\mathrm{Cof}}}[A - \lambda _i(A)1\!\!1]\right)&= \sum _{j=1}^n \, \prod \limits _{\begin{array}{c} k=1\\ k\ne j \end{array}}^n (\lambda _j-\lambda _i) = \prod \limits _{\begin{array}{c} k=1\\ k\ne i \end{array}}^n (\lambda _j-\lambda _i), \end{aligned}$$

where the second equality holds due to the fact that the product is zero if it contains the factor \((\lambda _i-\lambda _i)\). Hence this term is nonzero if and only if all eigenvalues of \(A\) are simple, in which case we can conclude that \(D\lambda _i(A).H = 0\) for all off-diagonal \(H\in {{\mathrm{Sym}}}(n)\).

Using these results, we can prove the following, which is a simple corollary to Proposition 2.5:

Corollary 7.2

Let \(f\in C^1(\mathbb {R})\), \(F\in C^2(\mathbb {R})\) with \(F'=f\) and let \(A\in {{\mathrm{Sym}}}(n)\) such that all eigenvalues of \(A\) are simple. Then the function

$$\begin{aligned} W: {{\mathrm{Sym}}}(n)\rightarrow \mathbb {R},\quad W(M) = \sum _{i=1}^n F(\lambda _i(M)) \end{aligned}$$

is differentiable at \(A\) with

$$\begin{aligned} DW[A] = f(A) = Q^T {{\mathrm{diag}}}(f(\lambda _1),\ldots ,f(\lambda _n)) \,Q, \end{aligned}$$

where \(A=Q^T {{\mathrm{diag}}}(\lambda _1,\ldots ,\lambda _n) \,Q\) is the spectral decomposition of \(A\).


According to Lemma 7.1, \(DW[Q^TXQ] = Q^TDW[X]Q\), hence we find

$$\begin{aligned} DW[A] = Q^T DW[{{\mathrm{diag}}}(\lambda _1,\ldots ,\lambda _n)] \,Q. \end{aligned}$$

Therefore it remains to show that

$$\begin{aligned} DW[{{\mathrm{diag}}}(\lambda _1,\ldots ,\lambda _n)].H = \left\langle {{\mathrm{diag}}}(f(\lambda _1),\ldots ,f(\lambda _n)),\, H \right\rangle \end{aligned}$$

for all \(H\in {{\mathrm{Sym}}}(n)\) and pairwise different \(\lambda _1,\ldots ,\lambda _n\).

We first consider the case of diagonal matrices \(H = H^{\mathrm {diag}}= {{\mathrm{diag}}}(h_1,\ldots ,h_n)\). Writing \(A^{\mathrm {diag}}= {{\mathrm{diag}}}(\lambda _1,\ldots ,\lambda _n)\) we find

$$\begin{aligned} W(A^{\mathrm {diag}}+tH^{\mathrm {diag}}) = W ({{\mathrm{diag}}}(\lambda _1+th_1,\ldots ,\lambda _n+th_n)) = \sum _{i=1}^n F(\lambda _i+th_i), \end{aligned}$$


$$\begin{aligned} DW[A^{\mathrm {diag}}].H^{\mathrm {diag}}&= \lim _{t\rightarrow 0} \,\frac{1}{t} \left( W(A^{\mathrm {diag}}+tH^{\mathrm {diag}})-W(A^{\mathrm {diag}}) \right) \nonumber \\&= \lim _{t\rightarrow 0} \,\frac{1}{t} \sum _{i=1}^n F(\lambda _i+th_i) - F(\lambda _i) = \sum _{i=1}^n F'(\lambda _i)\,h_i \nonumber \\&= \left\langle {{\mathrm{diag}}}(f(\lambda _1),\ldots ,f(\lambda _n)),\, {{\mathrm{diag}}}(h_1,\ldots ,h_n) \right\rangle = \left\langle f(A^{\mathrm {diag}}),\,H^{\mathrm {diag}} \right\rangle . \end{aligned}$$

Now let \(H=H^{\mathrm {off}}\) be a symmetric off-diagonal matrix, i.e. \(H^{\mathrm {off}}_{i,i}=0\) for \(i=1,\ldots ,n\). Using Eq. (20):

$$\begin{aligned} DW[A] = D\Psi [\lambda (A)] \cdot D\lambda [A], \end{aligned}$$

as well as the result of the previous considerations for diagonal \(A\) and off-diagonal \(H^{\mathrm {off}}\):

$$\begin{aligned} D\lambda [{{\mathrm{diag}}}(\lambda _1,\ldots ,\lambda _n)].H^{\mathrm {off}}= 0, \end{aligned}$$

we conclude

$$\begin{aligned} DW[{{\mathrm{diag}}}(\lambda _1,\ldots ,\lambda _n)].H^{\mathrm {off}}= 0. \end{aligned}$$

Finally, for arbitrary \(H\in {{\mathrm{Sym}}}(n)\), we can write \(H=H^{\mathrm {diag}}+H^{\mathrm {off}}\) with a diagonal matrix \(H^{\mathrm {diag}}\) and a symmetric off-diagonal matrix \(H^{\mathrm {off}}\). Then

$$\begin{aligned} DW[A^{\mathrm {diag}}].H&= DW[A^{\mathrm {diag}}].H^{\mathrm {diag}}+ DW[A^{\mathrm {diag}}].H^{\mathrm {off}}= DW[A^{\mathrm {diag}}].H^{\mathrm {diag}}\nonumber \\&= \left\langle f(A^{\mathrm {diag}}),\,H^{\mathrm {diag}} \right\rangle = \left\langle f(A^{\mathrm {diag}}),\,H \right\rangle , \end{aligned}$$

showing (24) and concluding the proof. \(\square \)

Rights and permissions

Reprints and Permissions

About this article

Verify currency and authenticity via CrossMark

Cite this article

Martin, R.J., Neff, P. Some remarks on the monotonicity of primary matrix functions on the set of symmetric matrices. Arch Appl Mech 85, 1761–1778 (2015).

Download citation


  • Primary matrix functions
  • Monotonicity
  • Constitutive inequalities
  • True-stress–true-strain inequality
  • Nonlinear elasticity